MODERN METHODS OF REPAIR OF PIPELINES - Martyniuk, R.T.; Chernova, O.T. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2022)
At the stages of maintenance and repair of pipeline systems, there is a need to use flameless cutting in existing pipelines, in particular: when it is necessary to connect intake chambers and start cleaning pistons, and during pipeline repair with a complete replacement of the pipe body without stopping the transportation of the product. Also, fireless cutting is effectively used to connect branch pipelines during the development of pipeline systems. One of the progressive directions of improving the maintenance and repair of pipelines is the development of cutting methods that would ensure high efficiency and environmental friendliness of the work. However, their successful application is impossible without a theoretical and experimental study of the process of welding the branch pipe to the operating pipeline.